2016
DOI: 10.3390/s16101575
|View full text |Cite
|
Sign up to set email alerts
|

Data Analytics for Smart Parking Applications

Abstract: We consider real-life smart parking systems where parking lot occupancy data are collected from field sensor devices and sent to backend servers for further processing and usage for applications. Our objective is to make these data useful to end users, such as parking managers, and, ultimately, to citizens. To this end, we concoct and validate an automated classification algorithm having two objectives: (1) outlier detection: to detect sensors with anomalous behavioral patterns, i.e., outliers; and (2) cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The study from Gomari et al [41] used parking events to model the parking behaviors in Munich. Different clustering methods can be applied to the smart parking data, and a comparative analysis is conducted by Piovesan et al [42]. By contrast, this study focuses on new parking meter data in Hong Kong, rarely studied in the existing literature.…”
Section: Data-driven Clustering Methodsmentioning
confidence: 99%
“…The study from Gomari et al [41] used parking events to model the parking behaviors in Munich. Different clustering methods can be applied to the smart parking data, and a comparative analysis is conducted by Piovesan et al [42]. By contrast, this study focuses on new parking meter data in Hong Kong, rarely studied in the existing literature.…”
Section: Data-driven Clustering Methodsmentioning
confidence: 99%
“…For example, in Cenedese et al (2014) and Zanella, Bui, Castellani, Vangelista, & Zorzi (2014), it is shown how malfunctioning street lights can be easily identified by simply comparing the standard deviation of the values read by the light sensors applied to the different light poles during nighttime. More advanced techniques can be used to extract interesting correlations among different signals and build advanced services (Piovesan, Turi, Toigo, Martinez, & Rossi, 2016).…”
Section: Extracting Informationmentioning
confidence: 99%
“…The parking process is modelled as a birth-death stochastic process which allows prediction and optimisation of parking availability. Piovesan et al [155] describe the application of their unsupervised form of self-organising maps (SOM) clustering to the classification of parking spaces according to spatio-temporal patterns. This type of analytics automatically discovers outliers for sensor maintenance and usage anomalies.…”
Section: Transport: Traffic Control and Routing Pedestrian Detection ...mentioning
confidence: 99%